Parasitic Helminth Community of the Puddingwife Wrasse Halichoeres radiatus (Linnaeus) in Reefs from Veracruz, Mexico - Montoya-Mendoza, Jesús; Morales-Sánchez, Georgina; Arenas-Fuentes, Virgilio E; González-Solis, David (The Journal of parasitology, 2021)
A total of 1,218 helminths ascribed to 11 taxa (6 at species, 3 at generic, 1 at family, and 1 at order level) in 101 specimens of Halichoeres radiatus (Pisces: Labridae) were caught in the Veracruz Coral Reef System National Park, southern Gulf of Mexico. These helminths include 4 trematode species (3 adults and 1 metacercaria), a cestode species (larvae), 5 nematode species (2 adults and 3 larvae), and an acanthocephalan species (juvenile). Nine correspond to new host records, 2 of them are new geographic records, and 6 species were recorded with 1 helminth per infected host. The larvae of Scaphanocephalus expansus (Creplin, 1842) Jägerskiöld, 1903, and larvae of the order Tetraphyllidea were the parasites with the highest prevalence and mean intensity. Species richness (S = 11) and the Shannon-Wiener diversity index (H′ = 1.1) were lower than those recorded for host-parasite communities in the locality. The fact that 10 of the total of 11 parasitic species were found in fish intestines suggests that infection is a result of host feeding habits.